Representasi Perempuan dalam Majalah Feminis Online Magdalene: Analisis Wacana Multimodal pada Postingan Instagram @Magdaleneid - Kurniati, Rima; Sawirman, Sawirman; Usman, Fajri (Lingua Susastra, 2025)
Women in media discourse are often marginalized, considered always wrong and given negative labels. The purpose of this study is to determine the representation of women in verbal texts and visual texts on the Instagram of the Magdalene Online Feminist Magazine. This study uses a qualitative method with a multimodal discourse analysis approach on the Instagram posts of the Magdalene Online Feminist Magazine. Verbal text analysis uses Halliday's Transitional Structure theory and visual text analysis uses Kress Leeuwen's Narrative Representation System. Data analysis is carried out through three stages including identification of processes, participants and circumstances, then multimodal interpretation and triangulation of findings. This study analyzes 42 illustrations from the Instagram account @magdaleneid selected using a purposive sampling technique from January to October 2024. The analysis is carried out in stages by identifying Halliday's transitivity structure in verbal texts and Kress Leeuwen's narrative representation system in visual texts, then interpreting the representational meaning of women based on the findings of both. The results of the study on verbal texts show that the dominant process is the material process, the dominant participants are actors and goals. The dominant circumstance is the cause circumstance. In the visual text, the most processes were action processes, the most participants were actors and goals, and the most circumstance was place circumstance. Verbal text analysis and visual text analysis show the representation of women in the Magdalene Online Feminist Magazine Instagram as active, dynamic subjects, and have important roles in various contexts. Verbal text analysis and visual text also have a complementary relationship and strengthen each other's meaning regarding the representation of women. This research adds to the literature on the analysis of transitivity structures, expands macrolinguistic studies, adds to media studies and gender studies.